1998
DOI: 10.1002/(sici)1521-396x(199809)169:1<67::aid-pssa67>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Structural Properties of Rapid Thermal Annealed Amorphous Silicon Carbide Films

Abstract: The effect of rapid thermal annealing (RTA) on radio frequency (rf) sputtered amorphous silicon carbide films prepared under different hydrogen partial pressures (PH) was examined. The structural study showed that the effect of RTA on the film properties was similar to that of furnace annealing. Therefore, the mechanisms suggested for furnace annealing could equally be applied to the RTA case. The electrical results showed that the effects of RTA and furnace annealing on interface trapped charge density (Dit) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The results of the work presented here also support earlier studies performed to investigate the crystallization of amorphous SiC films prepared by different film growth techniques [43][44][45].…”
Section: Discussionsupporting
confidence: 87%
“…The results of the work presented here also support earlier studies performed to investigate the crystallization of amorphous SiC films prepared by different film growth techniques [43][44][45].…”
Section: Discussionsupporting
confidence: 87%
“…This would result in lower connectivity in the layers and a temperature independent EPR linewidth. This analysis is supported by data on the electrical characterization of sputter deposited unhydrogenated a-SiC films that show a decrease in DC conductivity upon annealing [59]. Finally, the decrease in the value of DH pp as a function of T d for the annealing films (see Fig.…”
Section: Effect Of Annealingsupporting
confidence: 53%
“…In previous studies, authors have primarily utilized FTIR to determine either the hydrogen content or the concentration of some other single element in a dielectric material. In a few cases, other researchers have utilized previously published values for K SiC , K SiH , and K CH to calculate the total Si-C, Si-H, and C-H bond densities in a-SiC:H thin films [57,[60][61][62]. Unfortunately, in none of these reports were elemental or mass densities computed and/or cross calibrated to other techniques.…”
Section: Ftir Density and Elemental Composition Analysismentioning
confidence: 99%
“…Quantitative FTIR measurements of bond concentrations in a-SiC x and a-SiC x :H films have been reported by others [57][58][59][60][61][62]. These studies have typically relied on IR absorption cross sections reported for individual chemical bonds in non-SiC:H films.…”
Section: Introductionmentioning
confidence: 99%